Analisis Potensi dan Pengembangan Daya Tarik Wisata Pantai di Kota Semarang - Arifiana, Riska Dian; , Dr. Kuswaji Dwi Priyono, M. Si; , Dra. Umrotun, M. Si (2016)
The study with the title of "Potential Analysis and Development of Coastal Tourism in Semarang City" has 2 main objectives, namely (1) knowing the potential of coastal tourism attraction in Semarang City, and (2) knowing the development direction of coastal tourism attraction in Semarang City. Observation and field survey are the methods used in this study. Observation and field survey were conducted by giving a direct interview to the manager of the tourism sites also to the visitors that come by. The secondary data was obtained from the related agencies, governmental and non-governmental institutes in Semarang city. The analysis process used scoring technique for combining the internal and external potency. SWOT (Strengths, Weaknesses, Opportunities and Threats) analysis used to recognize the potential of coastal tourism and used to arrange the strategy for the future development. The results of this study show that Marina Beach has balance potential both internal and external which is in the medium category, meanwhile Maron Beach and Tirang Beach are in the low category. Based on the potential scores in the development process, Marina Beach is the first rank of coastal tourism attraction, the second is Maron Beach and the third is Tirang Beach. Marina Beach is the most popular beach in Semarang City because of its' location that lies in the main road, have accesibility, close to the city centre, and has many complete supporting facilities. Conversely, Maron Beach and Tirang Beach lack of interests because of the inadequate facilities such as the transportation accessibility and the remote locations. Development of tourism attractions could be done by maximised the coastal areas such as maintained and repaired the broken facilities, added more supporting facilities, infrastructures also made a collaboration either with the local government or the related non-governmental organisations.